AB0302 Results from the rate-ra study: a multicenter, open-label, single-arm study to evaluate the safety of administering rituximab at a more rapid infusion rate in patients with rheumatoid arthritis. (23rd January 2014) - Pritchard, C. H.; Greenwald, M. W.; Kremer, J. M.; Gaylis, N. B.; Zlotnick, S.; Chung, C.; Jaber, B.; Reiss, W.
Abstract : Background: The labelled dose of rituximab (RTX) in rheumatoid arthritis (RA) is 2 × 1000 mg IV infusions given 2 weeks apart (1 course), with recommended times of 4.25 hours (h) and 3.25h for infusions 1 and 2, respectively. Objectives: To assess the safety of administering the second infusion of an RTX course and subsequent infusions at a more rapid 2h rate. Methods: Patients with moderate-to-severe RA and an inadequate response to TNF inhibitors who were either RTX-naïve or RTX-experienced (up to 2 prior courses, last course 6–9 months before baseline) were eligible. All patients received methotrexate. The first infusion on Day 1 was at the standard rate. The second infusion on Day 15 was over 2h, as were infusions 3 and 4 (course 2) 6 months later. Premedication: IV methylprednisolone, antihistamine, analgesic prior to all RTX infusions. The primary endpoint was the incidence of infusion-related reactions (IRRs) during or within 24h of the second RTX infusion of course 1. Results: A total of 351 patients were enrolled. Mean age 55.6 (SD 11.5) y, with 19.9% of patients aged ≥65; mean RA disease duration 12.6 (SD 10.2) y. RTX-naïve (n=306; 87.2%); and RTX-experienced (n=45 of which 24 [6.8%] and 21 [6.0%] had received 1 or 2 prior RTX courses, respectively). All patients received the first RTX infusion at the standard rate; the incidence of IRRs (none serious) was 16.2% (95% CI: 12.5–20.5%), consistent with that derived from historical clinical trial data (20%). 1 Then 337 patients (96.0%) received a second RTX infusion at an increased rate: 331 completed the infusion and received the full 1000 mg dose (6 patients did not complete the infusion [3 for AE (none serious), 3 for other reasons]). Of these 331 patients, 5 (1.5%) required >2.5h. The incidence of IRRs for infusion 2 (primary endpoint) was 6.2% (95% CI: 3.9–9.4%) (21 patients experienced a total of 28 events), similar to historical data for infusion 2 given at the standard rate (7.8%). 1 All IRRs for infusion 2 were CTC grade 1 or 2 except one grade 3 (hypertension), with no grade 4 events. The most commonly observed IRRs for infusion 2 were nausea (1.2%) and chills (0.9%). No serious IRRs or SAEs were reported for infusions 1 or 2. Course 2 data indicate a low incidence of IRRs for infusions 3 and 4, with no serious IRRs or SAEs for both infusions. Safety events occurring during/within 24h of second RTX infusion (n=337). Conclusions: The incidence of IRRs occurring around the second infusion of RTX when administered at an increased 2h rate is similar to the historical incidence. The overall safety data were consistent with the known RTX safety profile. These data should have significant clinical relevance. References: van Vollenhoven et al. ACR 2012: poster 459 Disclosure of Interest: C. Pritchard Speakers bureau: Genentech Inc., M. Greenwald Grant/research support from: Genentech Inc., Roche, J. Kremer Grant/research support from: Genentech, Pfizer, HGS, UCB, BMS, Consultant for: Genentech, Pfizer, Abbott, Amgen, BMS, N. Gaylis Grant/research support from: Genentech Inc., Roche Products Ltd, Consultant for: Genentech Inc., Roche Products Ltd, S. Zlotnick Shareholder of: Roche, Employee of: Genentech Inc., C. Chung Employee of: Genentech Inc., B. Jaber Employee of: F. Hoffmann-La Roche Ltd, W. Reiss Employee of: Genentech Inc.